Using P-TOSCA to prevent vendor lock-in for cloud-based laboratories - Markoska, Elena; Kostoska, Magdalena; Ristov, Sasko; Gushev, Marjan (IEEE, 2015)
Distance laboratories are environment that can successfully replace the traditional physical laboratories. They allow the students to have practice even in arbitrary time. Many universities migrated their traditional laboratories in some cloud, staying locked there. In this paper we present a methodology of how to mitigate the risk of vendor lock-in for distance laboratories. We use the P-TOSCA model to describe the virtual laboratories placed in some virtual machines in the cloud, and by using the P-TOSCA engine we present how a cloud-based distance laboratory can be transferred to other cloud. We also present how to group virtual laboratories of several courses into one virtual machine, which will save the cloud resources and facilitate the cloud management.
Keywords: Cloud computing; portability; P-TOSCA